SOCIAL CONSTRUCTION OF MARRIAGE ON ADULT SINGLE WOMEN - Agnes Rumondang Marpaung; Eko Hartanto (LPPM Universitas Negeri Surabaya, 2023)
This study aims to find out the social construction of marriage is formed in Indonesian society and the perspective of single adult women on the social construction of marriage. This study uses a qualitative method by doing interviews with single adult women who do self-actualization and get the question